Institutional repositories and libraries: Being visible - Che Nasir, N.E. (2012)
The development of institutional repositories (IRs) is rampart and the task of developing and maintaining them is left to the university libraries. Most of the materials uploaded to the IRs are created by the staff of the university and therefore IRs now take the role of information disseminators on the academic activities of the university community. Many see IRs as a means of making a university visible through its publications and publishing activities and its presence helps to enhance the visibility of research as well as publications emanating from research. The traditional mode of scholarly publishing is seen by many as being too slow and is unable to keep up with STM research output. Within the university setting, the library is seen as the most suitable entity to propagate IRs. Libraries have always played a vital role in the information cycle and it is a natural progression for the library to manage as well as maintain an IR.